Gα(s) directly drives PDZ-RhoGEF signaling to Cdc42 - Castillo-Kauil, Alejandro (J Biol Chem, 2020)
Gα proteins promote dynamic adjustments of cell shape directed by actin-cytoskeleton reorganization via their respective RhoGEF effectors. For example, Gα(13) binding to the RGS-homology (RH) domains of several RH-RhoGEFs allosterically activates these proteins, causing them to expose their catalytic Dbl-homology (DH)/pleckstrin-homology (PH) regions, which triggers downstream signals. However, whether additional Gα proteins might directly regulate the RH-RhoGEFs was not known. To explore this question, we first examined the morphological effects of expressing shortened RH-RhoGEF DH/PH constructs of p115RhoGEF/ARHGEF1, PDZ-RhoGEF (PRG)/ARHGEF11, and LARG/ARHGEF12. As expected, the three constructs promoted cell contraction and activated RhoA, known to be downstream of Gα(13). Intriguingly, PRG DH/PH also induced filopodia-like cell protrusions and activated Cdc42. This pathway was stimulated by constitutively active Gα(s) (Gα(s)Q227L), which enabled endogenous PRG to gain affinity for Cdc42. A chemogenetic approach revealed that signaling by G(s)-coupled receptors, but not by those coupled to G(i) or G(q), enabled PRG to bind Cdc42. This receptor-dependent effect, as well as CREB phosphorylation, was blocked by a construct derived from the PRG:Gα(s)-binding region, PRG-linker. Active Gα(s) interacted with isolated PRG DH and PH domains and their linker. In addition, this construct interfered with Gα(s)Q227L's ability to guide PRG's interaction with Cdc42. Endogenous G(s)-coupled prostaglandin receptors stimulated PRG binding to membrane fractions and activated signaling to PKA, and this canonical endogenous pathway was attenuated by PRG-linker. Altogether, our results demonstrate that active Gα(s) can recognize PRG as a novel effector directing its DH/PH catalytic module to gain affinity for Cdc42.